Private healthcare quality: applying a SERVQUAL model - Butt, Mohsin; de Run, E. (Emerald Group Publishing, 2010)
Purpose – This paper seeks to develop and test the SERVQUAL model scale for measuring Malaysian private health service quality. Design/methodology/approach – The study consists of 340 randomly selected participants visiting a private healthcare facility during a three-month data collection period. Data were analyzed using means, correlations, principal component and confirmatory factor analysis to establish the modified SERVQUAL scale's reliability, underlying dimensionality and convergent, discriminant validity. Findings – Results indicate a moderate negative quality gap for overall Malaysian private healthcare service quality. Results also indicate a moderate negative quality gap on each service quality scale dimension. However, scale development analysis yielded excellent results, which can be used in wider healthcare policy and practice. Research limitations/implications – Respondents were skewed towards a younger population, causing concern that the results might not represent all Malaysian age groups. Originality/value – The study's major contribution is that it offers a way to assess private healthcare service quality. Second, it successfully develops a scale that can be used to measure health service quality in Malaysian contexts.